2012
DOI: 10.3109/02688697.2011.633640
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of acrylic and titanium cranioplasty#

Abstract: Although survival of acrylic cranioplasty appears to be better than titanium plates, there is no statistical significance. Acrylic has the advantage of being able to be applied at the time of surgery without any planning and does not cause artefact on future imaging. Titanium cranioplasty is strong, light-weight and inert and can be fashioned in the pre-operative setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
2
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 21 publications
0
44
2
3
Order By: Relevance
“…Infection rates of 5% to 20% are particularly elevated in the setting of frontal cranioplasty given sinus communication, risk for infection, and possible fistulization. 2,13,26,52,73,76,93 Complication rates quoted within the pediatric population reach as high as 23%, as reported by Blum et al in their 15-year retrospective review of 75 patients, with those patients with large defects, involvement of the frontal sinus, and any history of prior infection at the greatest risk. 13 Other rare but notable side effects of the material include delayed-type hypersensitivity reactions, which are seen in approximately 1% of patients.…”
Section: Acrylicsmentioning
confidence: 48%
“…Infection rates of 5% to 20% are particularly elevated in the setting of frontal cranioplasty given sinus communication, risk for infection, and possible fistulization. 2,13,26,52,73,76,93 Complication rates quoted within the pediatric population reach as high as 23%, as reported by Blum et al in their 15-year retrospective review of 75 patients, with those patients with large defects, involvement of the frontal sinus, and any history of prior infection at the greatest risk. 13 Other rare but notable side effects of the material include delayed-type hypersensitivity reactions, which are seen in approximately 1% of patients.…”
Section: Acrylicsmentioning
confidence: 48%
“…Another key advantage of titanium is its natural osseointegration factor, which promotes active bone growth into the implant [41,42]. Studies have shown that titanium implants for cranial and maxillofacial applications have a lower survival rate (higher complication rate) than alterative materials such as PMMA [27]. Despite its lower Young's modulus than alterative metals, the value for titanium is higher than that of natural bone, leading to a lessened, but still present, risk of stress shielding [79].…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, incidence of up to 20% described in medical literature should not be common. [1279141516171823] Moreover, once a cranioplasty flap is infected, usually flap removal is needed, which implicates a new surgery with bleeding and anesthetic risks, antibiotic treatment for at least 4 weeks, extending aesthetical disfiguring period and still requiring a new surgery to correct cranial defect and resulting in patient’s morbidity and hospital treatment costs increment.…”
Section: Discussionmentioning
confidence: 99%
“…Autologous bone cranioplasty has a lower incidence of postoperative infection when compared to synthetic prothesis, whose infection incidence may be as high as 20%. [127914151623] Even though surgeons apply all the procedures that significantly reduce postoperative infection, risks are applied (such as antiseptic preparation, use of sterilized matherials, adequate hand cleaning, and the use of antibiotic profylaxis during anesthesia induction), and the incidence of infection does not decrease from a certain percentage. No study has evaluated the impact over the infection incidence of antibiotic used in polymethylmethacrylate (PMMA) prothesis after cranioplasty.…”
Section: Introductionmentioning
confidence: 99%